Hubungan Nilai Rapor Biologi dengan Kompetensi Biologi Umum I Mahasiswa FMIPA Semester I T.P 2015/2016 Berdasarkan Jalur Masuk di Universitas Negeri Medan - Sinaga, Mery Tiurma; Manurung, Binari; Gultom, Tumiur (Jurnal Pendidikan Biologi, 2016)
This research aims are to determaine the relationship between raport value (X) and competence general biology I (Y) student college FMIPA level I T.P 2015/2016 based on the path to State University of Medan (SNMPTN, Bidikmisi, SBMPTN, UMB). This research is study using descriptive correlational. Population in this research were all the student FMIPAÂ  Level I of State University of Medan T.P 2015/2016 which amounted 1159 people. Sample was taken by Proportional Stratified Sampling obtained 176 people. Analysis techniques data is using multiple corellation. The study concluded that there was a relationship between raport value (X) and competence general biology I (Y), based on SBMPTN are 0.333 the regression equation Å¶ = 68.122 + 5.481 X1, SNMPTN are 0.117 the regression equation Å¶ = 18.093 + 0.363 X1, Bidikmisi are 0.188 the regression equation Å¶ = 1.662 + 0.017 X1, and UMB are -0.015 the regression equation Å¶ = 3.161 +(-0.001X1).